Magnitude, Severity, and Associated Factors of Anemia among Under-Five Children Attending Hawassa University Teaching and Referral Hospital, Hawassa, Southern Ethiopia, 2016 - Yeshimebet Gebereselassie; Mesganaw BirhanSelassie; Tadesse Menjetta; Jemal Alemu; Aster Tsegaye (Anemia)
Background. Anemia is a widespread public health problem associated with increased risk of morbidity and mortality. Infants, under-5-year-old children, and pregnant women have greater susceptibility to anemia. The magnitude and associated risk factors for anemia vary in different settings. The study aimed to assess the magnitude, severity, and associated factors of anemia at Hawassa University Teaching and Referral hospital, Hawassa, southern Ethiopia. Methods. In a hospital-based cross-sectional study, a total of 422 under-five children were included. Sociodemographic data and other predisposing factors were collected by structured questionnaire. Venous blood samples were collected and analyzed for hemoglobin determination using a Cell-Dyn 1800 automated analyzer. Stool samples were collected and processed using direct wet mount and formol-ether concentration method to detect intestinal parasites. Data were entered and analyzed using SPSS version 20 statistical packages. Binary and multiple logistic regressions were computed to assess factors associated with anemia. p value less than 0.05 was taken as statistically significant. Result. The overall prevalence of anemia was found to be 41.7%. The mean hemoglobin level was 10.59 g/dl. Anemia was of mild, moderate, and severe type in 6.6%, 19%, and 16.1% of the children, respectively. Children in the age group 6–23 months (AOR = 2.04 (95% CI: 1.13, 3.69)), and mothers having no formal education (AOR = 1.73 (95% CI: 0.99, 3.02)) were identified as associated factors for anemia. Conclusion. The prevalence of anemia among the study subjects was 41.7% indicative of the fact that anemia is an important public health problem. It was associated with the child’s age, residence, mother’s education level, and intestinal parasite (Ascaris lumbricoides). It clearly indicates that there should be well integrated public health interventions to improve the health status that needs to be prioritized to prevent anemia among children under five years of age.